2012
DOI: 10.4049/jimmunol.1102832
|View full text |Cite
|
Sign up to set email alerts
|

IL-33–Responsive Lineage−CD25+CD44hi Lymphoid Cells Mediate Innate Type 2 Immunity and Allergic Inflammation in the Lungs

Abstract: Innate immunity provides the first line of response to invading pathogens and a variety of environmental insults. Recent studies identified novel subsets of innate lymphoid cells that are capable of mediating immune responses in mucosal organs. Here we describe a subset of lymphoid cells that is involved in innate type-2 immunity in the lungs. Airway exposure of naïve BALB/c or C57BL mice to IL-33 results in a rapid (< 12 h) production of IL-5 and IL-13 and marked airway eosinophilia independently of adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
532
2
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(569 citation statements)
references
References 50 publications
25
532
2
10
Order By: Relevance
“…ILC2 are potently activated by the innate cytokines IL-33 and IL-25, and a vital role for these cells as a source of IL-13, required for the expulsion of intestinal helminths, has been determined (7,8,10). Furthermore, several groups reported an important role for ILC2 in allergy and airway inflammation and homeostasis (11)(12)(13)(14). We recently showed that transfer of ST2-expressing ILC2 into ST2-deficient mice was sufficient to mediate airway inflammation, mucus deposition, and cytokine production induced by administration of intranasal (i.n.)…”
mentioning
confidence: 99%
“…ILC2 are potently activated by the innate cytokines IL-33 and IL-25, and a vital role for these cells as a source of IL-13, required for the expulsion of intestinal helminths, has been determined (7,8,10). Furthermore, several groups reported an important role for ILC2 in allergy and airway inflammation and homeostasis (11)(12)(13)(14). We recently showed that transfer of ST2-expressing ILC2 into ST2-deficient mice was sufficient to mediate airway inflammation, mucus deposition, and cytokine production induced by administration of intranasal (i.n.)…”
mentioning
confidence: 99%
“…Because of their Th2 cytokine profile, they have been named group 2 ILCs (ILC2) and can be identified as lineage-negative cells expressing receptors for IL-2, IL-7, and IL-33 (4). The involvement of ILC2 in asthma was recently demonstrated in various mouse models, including HDM-driven allergic AAI (5)(6)(7)(8). ILC2 have also been identified in human lung and are associated with chronic rhinosinusitis (9)(10)(11).…”
mentioning
confidence: 99%
“…Although the cellular source of IL-17A in J H 2/2 mice during A. fumigatus infection remains unknown, recent studies suggest that macrophages or innate lymphoid cells might contribute to early IL-17 production in allergic asthma. 38,57,59,61 This observation highlights the need for further research to clarify the role of IL-17A in fungal asthma.…”
Section: Fungal Conidia Inhalation Significantly Increases Collagen Dmentioning
confidence: 98%